2020
DOI: 10.3390/biom10020305
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals in Garlic Extract Inhibit Therapeutic Enzyme DPP-4 and Induce Skeletal Muscle Cell Proliferation: A Possible Mechanism of Action to Benefit the Treatment of Diabetes Mellitus

Abstract: Diabetes mellitus is a severe health problem in Mexico, and its prevalence is increasing exponentially every year. Recently, DPP-4 (dipeptidyl peptidase-4) inhibitors have become attractive oral anti-hyperglycemic agents to reduce the pathology of diabetes. Gliptin’s family, such as sitagliptin, vildagliptin, and alogliptin, are in clinical use to treat diabetes mellitus but possess side effects. Therefore, there is a specific need to look for new therapeutic scaffolds (biomolecules). Garlic bulb is widely use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 59 publications
1
30
0
Order By: Relevance
“…Whereas, the treatments of the test extract (W. coagulans fruit ethanol extract) and standard drug caused signi cant reductions in glucose, insulin and HOMA indices resulted in improvements in glucose homeostasis and increased pancreatic β-cell mass. These kinds of results may follow the interaction with DPP-4 by possesses active metabolites (phytochemicals) of extract through prolonging the GLP-1 postprandial stimulation to pancreatic tissues as reported by several studies [54,55]. Accordingly, the results of LCMS analysis shown that occurrence of potent bioactive phytocompounds in ethanol fruit extract of Withania coagulans known as withanoids, including withanolide D, sitoindoside IX, withanoside IV, withanone, withanolide B, withaferin A, withasomnine, withangulatin A, withacoagulin H, and withanolide E. Subsequently, the invitro assay of the test extract against DPP-4 performed the 63.2% inhibition which validate the interaction with target enzyme (DPP-4) and phytocompounds.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Whereas, the treatments of the test extract (W. coagulans fruit ethanol extract) and standard drug caused signi cant reductions in glucose, insulin and HOMA indices resulted in improvements in glucose homeostasis and increased pancreatic β-cell mass. These kinds of results may follow the interaction with DPP-4 by possesses active metabolites (phytochemicals) of extract through prolonging the GLP-1 postprandial stimulation to pancreatic tissues as reported by several studies [54,55]. Accordingly, the results of LCMS analysis shown that occurrence of potent bioactive phytocompounds in ethanol fruit extract of Withania coagulans known as withanoids, including withanolide D, sitoindoside IX, withanoside IV, withanone, withanolide B, withaferin A, withasomnine, withangulatin A, withacoagulin H, and withanolide E. Subsequently, the invitro assay of the test extract against DPP-4 performed the 63.2% inhibition which validate the interaction with target enzyme (DPP-4) and phytocompounds.…”
Section: Discussionmentioning
confidence: 75%
“…In same context, it is illustrated that the phytocompounds have the ability to inhibit speci c enzymes by binding to the active site within the enzyme molecule or a related mode of action [56,57]. Ideal inhibitors have a low molecular weight that can reduce or completely inhibit enzyme activity at low concentrations [55]. Several human enzyme inhibitors, such as antithrombin and antitrypsin, control enzyme activity in the body, and can function under normal physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, the treatments of the test extract ( W. coagulans fruit ethanol extract) and standard drug caused significant reductions in glucose, insulin and HOMA indices resulted in improvements in glucose homeostasis and increased pancreatic β-cell mass. These kinds of results may follow the interaction with DPP-4 by possesses active metabolites (phytochemicals) of extract through prolonging the GLP-1 postprandial stimulation to pancreatic tissues as reported by several studies [ 54 , 55 ]. Accordingly, the results of LCMS analysis shown that occurrence of potent bioactive phytocompounds in ethanol fruit extract of W coagulans known as withanoids, including withanolide D, sitoindoside IX, withanoside IV, withanone, withanolide B, withaferin A, withasomnine, withangulatin A, withacoagulin H, and withanolide E. Subsequently, the in-vitro assay of the test extract against DPP-4 performed the 63.2% inhibition which validate the interaction with target enzyme (DPP-4) and phytocompounds.…”
Section: Discussionmentioning
confidence: 79%
“…Whereas, the treatments of the test extract (W. coagulans fruit ethanol extract) and standard drug caused signi cant reductions in glucose, insulin and HOMA indices resulted in improvements in glucose homeostasis and increased pancreatic β-cell mass. These kinds of results may follow the interaction with DPP-4 by possesses active metabolites (phytochemicals) of extract through prolonging the GLP-1 postprandial stimulation to pancreatic tissues as reported by several studies[52,53]. Accordingly, the results of LCMS analysis shown that occurrence of potent bioactive phytocompounds in ethanol fruit extract of Withania coagulans known as withanoids, including withanolide D, sitoindoside IX, withanoside IV, withanone, withanolide B, withaferin A, withasomnine, withangulatin A, withacoagulin H, and withanolide E. Subsequently, the invitro assay of the test extract against DPP-4 performed the 63.2% inhibition which validate the interaction with target enzyme (DPP-4) and phytocompounds.In same context, it is illustrated that the phytocompounds have the ability to inhibit speci c enzymes by binding to the active site within the enzyme molecule or a related mode of action(Akhtar et al 2018; Lankatillake et al 2019).…”
mentioning
confidence: 75%
“…Accordingly, the results of LCMS analysis shown that occurrence of potent bioactive phytocompounds in ethanol fruit extract of Withania coagulans known as withanoids, including withanolide D, sitoindoside IX, withanoside IV, withanone, withanolide B, withaferin A, withasomnine, withangulatin A, withacoagulin H, and withanolide E. Subsequently, the invitro assay of the test extract against DPP-4 performed the 63.2% inhibition which validate the interaction with target enzyme (DPP-4) and phytocompounds.In same context, it is illustrated that the phytocompounds have the ability to inhibit speci c enzymes by binding to the active site within the enzyme molecule or a related mode of action(Akhtar et al 2018; Lankatillake et al 2019). Ideal inhibitors have a low molecular weight that can reduce or completely inhibit enzyme activity at low concentrations(Kalhotra et al 2020). Several human enzyme inhibitors, such as antithrombin and antitrypsin, control enzyme activity in the body, and can function under normal physiological conditions.…”
mentioning
confidence: 99%